Synthesis of the Ag2S/PANIPES Composite Membrane and Its Antipollution Properties - Li, Ruiqi (Langmuir : the ACS journal of surfaces and colloids, 2024)
Membrane separation technology offers a sustainable and efficient solution to wastewater management; however, membrane fouling significantly impedes its application. Photocatalytic membranes, integrating photocatalytic and membrane separation technologies, enhance membrane separation efficacy while effectively mitigating organic and biological contaminations. In this work, Ag2S/PANIPES composite membranes were prepared via a facile in situ polymerization and successive layer adsorption technique. The modified poly(ether sulfone) (PES) membrane demonstrated improved hydrophilicity and separation performance, and its heterostructure between polyaniline (PANI), Ag0, and Ag2S effectively addressed organic fouling issues. Moreover, Ag2S/PANI@PES exhibited outstanding antimicrobial properties, as well as chemical and mechanical stability